2018
DOI: 10.1177/1178636118758651
|View full text |Cite
|
Sign up to set email alerts
|

Viral and Bacterial Etiologies of Acute Respiratory Infections Among Children Under 5 Years in Senegal

Abstract: Acute respiratory infections (ARIs) are the leading cause of infectious disease–related morbidity, hospitalization, and morbidity among children worldwide. This study aimed to assess the viral and bacterial causes of ARI morbidity and mortality in children under 5 years in Senegal. Nasopharyngeal samples were collected from children under 5 years who had ARI. Viruses and bacteria were identified using multiplex real-time reverse transcription-polymerase chain reaction and conventional biochemical techniques, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 17 publications
4
38
0
1
Order By: Relevance
“…From a total of 288 samples analyzed from children under 5 years old with a probable diagnosis of Pertussis, the most common pathogen isolated was ADV in 49% of samples, followed by B. pertussis in 41% from our previous analysis. Although this study was conducted in patients with ARI with a highly suspicious pertussis diagnosis, other studies on children with ARI have identified ADV as one of the most prevalent etiologies [2] Although, the viral and bacterial prevalence may vary widely depending on the population characteristics [8,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From a total of 288 samples analyzed from children under 5 years old with a probable diagnosis of Pertussis, the most common pathogen isolated was ADV in 49% of samples, followed by B. pertussis in 41% from our previous analysis. Although this study was conducted in patients with ARI with a highly suspicious pertussis diagnosis, other studies on children with ARI have identified ADV as one of the most prevalent etiologies [2] Although, the viral and bacterial prevalence may vary widely depending on the population characteristics [8,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…ARIs as the most common cause of morbidity and mortality in children, remaining a major concern, especially affecting children under 5 years old from low-income countries [1][2][3][4]. Unfortunately, information regarding their epidemiology is still limited in Peru [7,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations